Irritable bowel syndrome: frequency and phylogenetic relationship of Blastocystis sp. from Mexican patients - Ramírez-Miranda, M E; Jiménez-González, D E; Rodríguez-Campa, M E; González-Angulo, A; Hernández-Castellanos, R; Sara Arroyo-Escalante, A; Romero-Valdovinos, M; Martínez-Hernández, F; Flisser, A; Maravilla, P (Revista de gastroenterología de México, 2011)
Recent studies reported increased presence of Blastocystis in patients with Irritable Bowel Syndrome (IBS) and an etiologic role has been proposed. The pathogenic role of Blastocystis is controversial, because it is frequently found not only in individuals with enteric symptoms but also in healthy and asymptomatic subjects. Furthermore, there are few studies of blastocistosis in Mexico. To assess the frequency of Blastocystis sp. in IBS patients using molecular techniques and to describe its phylogenetic relationship with sequences of other countries. IBS patients according to Rome III criteria were enrolled. In all patients evaluations included: colonoscopies, coproparasitoscopic studies, coproculture, fecal virus screening. PCR and sequencing for Blastocystis sp. were also performed. We recruited 11 men and 51 women with a mean age of 45.6 (SD ± 15.7) years. Eighty-six percent of the IBS patients presented a normal colonoscopy, 8% showed polyps and 6% diverticular disease. Blastocystis sp. was identified in 25% patients (all of them with normal colonoscopy), while two patients had Endolimax nana and Entamoeba histolytica/E. dispar, respectively. Phylogenetic analysis showed that major sequences of Mexican carriers clustered together with sequences of parasites from Japan and Denmark; furthermore, two sequences from IBS patients were grouped in a single cluster. Blastocystis sp. was identified in 25% of the IBS patients. Our data support the hypothesis of clonal lineages in distinct geographical areas in the world.